Human sperm heads harbor modified YsRNA as transgenerationally inherited non-coding RNAs - Elzer, Darja; Bremser, Michelle; Zischler, Hans (Frontiers in Genetics, 2023)
Most epigenetic information is reprogrammed during gametogenesis and early development. However, some epigenetic information persists and can be inherited, a phenomenon that is common in plants. On the other hand, there are increasing examples of epigenetic inheritance in metazoans, especially for small non-coding RNAs. The presence of regulatory important RNAs in oocytes is undisputed, whereas the corresponding RNA payload in spermatozoa and its regulatory influence in the zygote and early embryogenesis is largely enigmatic. For humans, we herein describe small YRNA fragments (YsRNA) as paternal contribution to the zygote. First, we trace the biogenesis of these YsRNAs from source YRNAs with respect to the 5’ and 3’ modifications. Both the length and modifications make these YsRNAs reminiscent of canonical piRNAs that are not derived from piRNA clusters. Second, from the early stages of spermatogenesis to maturation in the epididymis, we observe distinct YsRNA-profile dynamics in the male germline. We detected YsRNAs exclusively in mature sperm heads, the precursor of the male pronucleus in the zygote, suggesting an important role of the epididymis as a site for transmitting and modification of epigenetic information in the form of YsRNA between soma and germline in humans. Since this YsRNA-based epigenetic mechanism is effective across generations, we wondered whether this phenomenon of epigenetic inheritance has adaptive value. Full-length YRNAs bind to Ro60, an RNA chaperone that additionally binds non-coding RNAs. We described the profiles of non-coding RNAs bound to Ro60 in the human sperm head and detected specific binding profiles of RNA to Ro60, but no YRNA bound to Ro60. We hypothesize that the sperm head Ro60 system is functional. An adaptive phenotype mediated by the presence of a large amount of YsRNA in the sperm head, and thus as a paternal contribution in the zygote, might be related to an association of YsRNA with YRNA that prevents the adoption of a YRNA secondary structure capable of binding Ro60. We hypothesize that preventing YRNAs from acting as Ro60-associated gatekeepers for misfolded RNAs in the zygote and early development may enhance RNA chaperoning and thus represent the adaptive molecular phenotype.